Nonoperative management of rectal cancer after chemoradiation opposed to resection after complete clinical response. A comparative study. Issue 11 (November 2015) - Araujo, R.O.C.; Valadão, M.; Borges, D.; Linhares, E.; de Jesus, J.P.; Ferreira, C.G.; Victorino, A.P.; Vieira, F.M.; Albagli, R.
Abstract: Introduction: Surgery is the standard treatment of rectal cancer after neoadjuvant therapy. Some authors advocate a nonoperative management (NOM) after complete clinical response (cCR) following chemoradiotherapy (CRT). We compare our results with NOM to standard resection in a retrospective analysis. Methods: Rectal adenocarcinomas submitted to NOM after CRT between September 2002 and December 2013 were compared to surgical patients that had pathological complete response (pCR) during the same period. Endpoints were Overall Survival (OS), Disease Free Survival (DFS), Local Relapse (LR) and Distant Relapse (DR). Results: Forty-two NOM patients compared to 69 pCR patients operated after a median interval of 35 weeks after CRT. NOM tumors were distal (83.3% vs 59.4%, p = 0.011), less obstructive (26.2% vs 54.4%, p = 0.005) and had a lower digital rectal score (p = 0.024). Twelve (28.0%) recurrences in NOM group and eight (11.5%) in the surgical group occurred after a follow-up of 47.7 and 46.7 months respectively. Isolated LR occurred in five (11%) NOM patients and one (1.4%) in the surgical group. Four (80%) LR were surgically salvaged in NOM group. No difference in OS was found (71.6% vs 89.9%, p = 0.316) but there was a higher DFS favoring surgical group (60.9% vs 82.8%, p = 0.011). Distal tumors had worse OS compared to proximal tumors in surgical group (5-year OS of 85.5% vs 96.2%, p = 0.038). Conclusion: The NOM achieved OS comparable to surgical treatment and spared patients from surgical morbidity but it resulted in more recurrences. This approach cannot be advocated routinely and controlled trials are warranted.